Aplicación de las metodologías de observación directa e indirecta para el monitoreo del lobo andino (Lycalopex culpaeus), para determinar su presencia en los páramos de la parroquia de Tanicuchí. - Mullo Silva, Gabriela Estefania (2022)
The purpose of this research is to determine the presence of the Andean wolf (Lycalopex culpaeus) in the moors of the Tanicuchí parish, Latacunga canton, Cotopaxi Province, through constant monitoring with direct and indirect techniques that will facilitate the search for it. The study was carried out in the Samilpamba sector at 3,561.1 meters above sea level and the Cunuyacu sector at 3,768.4 meters above sea level, taking into account different geo-positional points in the surroundings in a period of 4 months between April 2022 and August 2022. Emphasis was placed on use direct monitoring techniques such as linear transects to delimit the study areas and therefore 5 transects were carried out at strategic points in the places mentioned, thus allowing the collection and registration of signs that denote the presence of the species that interests us. . Resulting in the sighting of signs of animals such as feral dogs, rabbits, cattle and the Andean wolf. Obtaining with this a total of 14 signs between excreta, tracks and beds/burrows at heights of 3561.1 masl, 3669.1 masl, 3676.1 masl, 3656.5 masl and 3680.9 masl belonging to the town of Samilpamba; in turn 3768.4 meters above sea level and 3688 meters above sea level corresponding to the Cunuyacu sector, which, according to the literature, is not enough to determine the fixed presence of this animal in the Tanicuchí sector. In turn, the presence of feral canids that were witnessed by the resident population in these places was determined, which is considered one of the factors that limits the habitat of Lycalopex culpaeus.